2017
DOI: 10.1159/000477271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on the Association of Vascular Access Type with Mortality in a Cohort of Incident End-Stage Renal Disease Patients

Abstract: Background/Aims: All hemodialysis (HD) patients are generally recommended to create a fistula first; but to create a mature arteriovenous fistula (AVF) can be challenging in elderly individuals. It is unclear if elderly incident HD patients derive a survival benefit from an AVF over an arteriovenous graft (AVG) or a tunneled central venous catheter (TDC). Methods: We examined the association of vascular access type (AVF, AVG, and TDC with and without a maturing AVF/AVG at dialysis transition) at HD initiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
1
18
1
1
Order By: Relevance
“…In addition, wearing a catheter enhances the risk of mortality more than 12‐fold, even after adjustment for several variables. The choice of a vascular access different from an autologous fistula leads to many complications including infections and dysfunction 19 . The first one contributes to higher rates of hospitalizations and mortality but our study suggests that catheter predicts mortality independently from reason for admission and comorbidities 20 …”
Section: Discussionmentioning
confidence: 74%
“…In addition, wearing a catheter enhances the risk of mortality more than 12‐fold, even after adjustment for several variables. The choice of a vascular access different from an autologous fistula leads to many complications including infections and dysfunction 19 . The first one contributes to higher rates of hospitalizations and mortality but our study suggests that catheter predicts mortality independently from reason for admission and comorbidities 20 …”
Section: Discussionmentioning
confidence: 74%
“…patients who initiated hemodialysis with a functioning AVF/ AVG may have had better access to or compliance with predialysis nephrology care). It has been suggested that patients' underlying conditions during the predialysis period have a greater impact on outcomes than the effect of access itself [18,42,43], and the survival benefits of AVFs/AVGs over CVCs may be minimal among patients who are at higher risk of AVF/ AVG failure (i.e. older age, female, diabetic) [44].…”
Section: Discussionmentioning
confidence: 99%
“…While associated with better clinical outcomes in the general hemodialysis population [6][7][8][9], use of arteriovenous fistulas (AVFs) in elderly hemodialysis patients poses unique challenges given their higher rates of inadequate maturation of vascular access and limited life expectancy [10][11][12]. Moreover, there remains wide debate as to whether the Fistula First Breakthrough Initiative should be applied to the elderly hemodialysis population [12][13][14][15], given operational risks, longer maturation times and emerging data indicating the lack of a survival benefit compared with tunneled dialysis catheter [central venous catheter (CVC)] and/or arteriovenous graft (AVG) use in elderly patients [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…15,16 The superiority of permanent access has been specifically demonstrated in the elderly. 7,12,17 It has been suggested that AVGs may be favorable in older populations with more comorbidities and shorter life expectancies, due to the extended maturation time of AVFs. 18,19 However, conflicting research findings showed AVFs to have similar or better outcomes as prosthetic AVGs in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that age has no significant impact on catheters and AV access outcomes, with older patients having comparable outcomes to their younger counterparts. 12,13 Others have concluded that the benefit of AV access for HD decreases with advancing age, as older patients in those studies were found to have lower maturation rates, higher rates of reintervention, and lower patency rates. 5,7e10,14 In addition, there are limited data to guide access creation in octogenarians.…”
Section: Introductionmentioning
confidence: 99%